St. John’s Wort Extract Increases Pgp Expression in the Brain but Not in the Small Intestine or the Liver of Wistar Rats - Valerio Taggi; Anima M. Schäfer; Isabell Seibert; Henriette E. Meyer zu Schwabedissen (Pharmacology Research & Perspectives)
ABSTRACT St John's Wort (SJW), commonly used to treat mild depression, is known to pose a risk of drug–herb interactions through hyperforin‐mediated activation of the pregnane X receptor (PXR). This induces transcription and expression of PXR target genes, including the efflux transporter P‐glycoprotein (Pgp). While the activation of human PXR by the SJW constituent hyperforin is well established, there are contradictory findings on rodent PXR target genes. This study aimed to further investigate SJW effects on Pgp expression in rats. Male Wistar rats were treated for 10 days with the two commercial SJW formulations, Hyperiplant and Rebalance, which differ in their hyperforin content. Quantitative real‐time PCR, western blot analysis, and immunohistochemical staining were applied to test for Pgp mRNA expression and protein abundance in the small intestine (jejunum), liver, and brain (cerebrum). Treatment with the hyperforin‐rich Hyperiplant increased protein levels in the brain. However, it did not affect mRNA levels. Besides, there was no impact on Pgp protein abundance in the small intestine or the liver. The hyperforin‐poor formulation Rebalance did not affect Pgp expression in any of the investigated tissues. Taken together, our results show that there is a modulation of brain Pgp protein abundance in Hyperiplant‐treated animals. As such, we conclude that the inducing effect is governed by a so far unknown regulatory mechanism that most likely does not affect transcription of the transporter.